Analisis Tindak Tutur Lokusi Bertema Hewan dalam Kanal YouTube Sisi Terang - Syafira Oktavia Pramesti; Akhmar Aribuma; Fahmi Nur Hidayana; Ricky Febianto; Elis Listiani; Fifi Auliya Hakiki; Asep Purwo Yudi Utomo; Rosita Rahma (Populer: Jurnal Penelitian Mahasiswa, 2025)
The rapid development of language means that young people, such as students, must understand the proper and correct use of language. People need information for learning and entertainment purposes. For this reason, educational viewing is needed to uphold the factuality and up-to-dateness of the information on YouTube. This research focuses more on analyzing facts about animals, in addition to analyzing elocutionary speech acts in videos. This research is based on two reasons, namely practical and theoretical reasons. For practical reasons for conducting this research, it was found that many elocutionary speech acts on the Sisi Terang YouTube channel had an animal theme, in the playlist, we found discussions about animal facts. Apart from that, this research was conducted to provide information about things correlated with illocutionary speech acts, which are widel implemented in human life and can classify the form, function, and types of illocutionary speech acts. Qualitative research is included in this research methodology so that it can produce descriptive data. The techniques used in this research are note-taking techniques and pragmatic analysis techniques to produce data. Matched data and collection techniques are also used in this analysis when presented as formal and informal data. Based on the study on the Bright Side YouTube Channel with an Animal Theme in the Form of Locutionary Speech Acts, 62 news sentences, 32 question sentences, and 49 command sentences were found. In addition to being used in this research to analyze the form of illocutionary speech acts on the Animal-Themed Bright Side YouTube Channel, this research also has the benefit of adding new insight into the study of pragmatics, specifically in the use of social media.